Lymphoedema: non-operative management - Sukhadia, Mukta; Sethi, Deepak; Sethi, Anjali (International Surgery Journal, 2018)
Background: Lymphoedema is one of the most undesirable complication that is anticipated in patients of cancer breast post mastectomy. A comprehensive care of patient of lymphoedema is required which includes, prevention, early diagnosis and treatment. In the study conducted, efficacy of non-operative management of lymphoedema is observed. Methods: A descriptive study was conducted on women who presented with lymphoedema post-mastectomy. Thirty-three patients were studied for non-operative management. Treatment of patients was carried out with physiotherapy, massage, compression bandages and stockings and Intermittent pneumatic compression by pneumatic compression pump. Results: Patients were categorized according to the grades, duration of lymphoedema, type of treatment they received and effect of the treatment. Conclusions: Lymphoedema being dreaded complication, much attention needs to be given on its prevention post mastectomy. But in country like India, compliance and regular follow up is not possible for every patient, especially for the patients of the rural background. The same pattern of dearth in compliance follows in management of lymphoedema. Non-operative management is an effective mode of treatment in cases of post-mastectomy lymphoedema.